ANALISIS STRATEGI PENGEMBANGAN EKONOMI LOKAL MASYARAKAT PESISIR DI DESA LABUHAN BAJO - Ayunda, Irdian Okri Prio; Sumbawati, Novi Kadewi; Pamungkas, Binar Dwiyanto Pamungkas (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2024)
This research aims to analyze strategies for optimizing local economic development (PEL) in Labuhan Bajo village, Utan sub-district, Sumbawa district. The research sample was 30 respondents related to local economic development strategies. The data used in this research uses primary data and secondary data, where data is taken by observasing and distributing questionnaires directly with respondents or the best experts and obtaining a clear understanding from existing literature. The analysis technique uses the process hierarchy analysis (AHP) method with the help of the expert choice application. The results of this research show that the priority strategies for optimizing local economic development in Labuhan Bajo village include : 1) Human Resources, 2) The role of government and society, 3) Regional marketing, 4) Capital, 5) Natural resources, 6) Techology. Keywords: Development; Local economy; coastal; strategy